2021
DOI: 10.1002/ptr.7152
|View full text |Cite
|
Sign up to set email alerts
|

Rotundic acid reduces LPS‐induced acute lung injury in vitro and in vivo through regulating TLR4 dimer

Abstract: Acute lung injury (ALI) is a serious clinical disease. Rotundic acid (RA), a natural ingredient isolated from Ilex rotunda Thunb, exhibits multiple pharmacological activities. However, RA's therapeutic effect and mechanism on ALI remain to be elucidated. The present study aimed to further clarify its regulating effects on inflammation in vitro and in vivo. Our results indicated that RA significantly inhibited the overproduction of interleukin‐6 (IL‐6), tumor necrosis factor‐α (TNF‐α), cyclooxygenase‐2 (COX‐2),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…However, HSC effectively inhibits this NF‐kB/p65 nuclear translocation, as confirmed by immunofluorescence data (Figure 3h,i). The activation of the NF‐κB signaling pathway leads to the production of pro‐inflammatory factors like TNF‐α and IL‐6 (Li, Yuan, et al, 2021). RT‐qPCR, as shown in Figure 3f,g, was used to study the impact of HSC on the release of TNF‐α and IL‐6.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, HSC effectively inhibits this NF‐kB/p65 nuclear translocation, as confirmed by immunofluorescence data (Figure 3h,i). The activation of the NF‐κB signaling pathway leads to the production of pro‐inflammatory factors like TNF‐α and IL‐6 (Li, Yuan, et al, 2021). RT‐qPCR, as shown in Figure 3f,g, was used to study the impact of HSC on the release of TNF‐α and IL‐6.…”
Section: Resultsmentioning
confidence: 99%
“…This action triggers the discharge of calcium ions from internal storage or stimulates PKC to control subsequent signaling processes (Suh et al, 2008). The activation of the NF-κB signaling pathway leads to the production of pro-inflammatory factors like TNF-α and IL-6 (Li, Yuan, et al, 2021). RT-qPCR, as shown in Figure 3f,g, was used to study the impact of HSC on the release of TNF-α and IL-6.…”
Section: Hsc Suppresses Nlrp3 Inflammasome Activation In Lps + Atp-in...mentioning
confidence: 99%
“…A recent study has shown that CYR61 can promote the expression of TLR4, 31 while TLR4 is widely involved in promoting acute lung injury. [32][33][34] The stated study indicated that TLR4/MYD88 signaling pathway was activated by induction of LPS, which was suppressed by the interference of KLF6. Consistent with the previous study, 31 overexpression of CYR61 promoted the expressions of TLR4 and MYD88 in LPS-induced A549 cells transfected with Si-KLF6.…”
Section: Cyr61 Overexpression Reversed the Inhibitory Effect Of Inter...mentioning
confidence: 94%
“…The study also revealed that RA obstructed the activation of the PI3K, MAPK, and NF-kB pathways while enhancing the activity of the Nrf2 signaling pathway. [80] The antioxidant and anti-inflammatory effects of RA and their molecular mechanisms are clarified in Table 2.…”
Section: Anti-inflammatory Activitymentioning
confidence: 99%